Assessment of health risks associated with water-borne diseases due to flooding in the Kwilu River Valley in Kikwit, Democratic Republic of the Congo - MUNDUKU, Midishi Olivier; Kikozokozo, Kikozokozo Dieudonne; KILENSELE, Muwele Thérèse; BANGANGA, Gedeon Gedeon; KALELA, Ilunga Thérèse; BONDO, Banza Steve; KILENSELE, Eyul’anki Dieudonne; MPURU, Mazembe Bias (Orapuh Journal, 2024)
Introduction Flooding poses a socio-environmental threat by introducing water to areas usually dry, thereby facilitating the spread of various pathogens. Flood-prone areas are vulnerable to numerous health risks, often resulting in fatalities, especially among children under five and pregnant women. Purpose This study aims to assess the health risks associated with water-borne diseases caused by flooding in the Kwilu River Valley in Kikwit. Methods This research employs a cartographic approach combined with experimentation and descriptive observation to analyze a non-probabilistic sample. Results Climatic and geomorphological factors are the primary natural causes of flooding in the Kwilu River Valley. Socio-environmental vulnerabilities among residents in the study area contribute significantly to the health risks associated with flooding. Malaria is the most prevalent water-borne disease in the Kwilu Valley, followed by diarrhoea, pneumonia, and typhoid fever. Conclusion The health risks associated with flooding in the Kwilu River Valley in Kikwit are substantial. Pathological surveillance, enhanced drainage systems, and expanded public health campaigns are essential to promote improved living conditions for the community.